Quantifying trunk impact dynamics and workload with inertial sensors in goalball players - Comeras-Chueca, C.; Bascuas, P. J.; Berzosa, C.; Piedrafita, E.; Rabal-Pelay, J.; Gutiérrez, H.; Bataller-Cervero, A. V. (Sports, 2024)
The aim of this study was to quantify trunk impact dynamics in goalball players using inertial sensors and evaluate the goalball players` workloads, focusing on changes between the first and second halves of a match to enhance understanding of the demands experienced throughout the game. Utilizing inertial technology, trunk impacts during goalball gameplay were analyzed to provide a holistic insight into how these impacts influence athletes` dynamic stress loads, which refers to the physical demands placed on the body during dynamic movements. Six goalball players were recruited to wear an accelerometer during a whole goalball game to quantify trunk impacts. The results showed a higher number of total impacts and a higher number of impacts at higher levels during the first half, compared to a higher percentage of impacts at a low impact level in the second half. These results suggest that the intensity of gameplay is related to the number of impacts sustained, with players experiencing significantly more impacts, particularly at very low, low, and very high impact levels, in the first half compared to the second half. This decline in impacts aligns with the reduction in game intensity as the match progressed, as indicated by a lower heart rate and a trend towards a lower dynamic stress load in the second half. Future research could explore targeted training interventions aimed at optimizing workload and performance in goalball players.